2015
DOI: 10.12816/0011214
|View full text |Cite
|
Sign up to set email alerts
|

Security Challenges and the Implications for Business Activities in Nigeria : A Ctritical Review

Abstract: This paper examines security challenges and the implications for business activities in Nigeria. The paper seeks to determine the implications of security problems on the business operation and investment in Nigeria. The study adopts the Democratic Peace Theory. Secondary data was mostly used in the study. The study identifies the root causes of insecurity in Nigeria which has hindered business activities and some Security challenges confronting Nigeria was also highlighted. Security challenges in any environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…A similar study by Olusegun (2016) shows that security and other related variables do not only contribute positively to economic growth in Nigeria. In the same vein, Ifeoma, Ndubuisi-Okolo and Anagbogu (2015) reached the same conclusion emphasizing that security challenges retards the socio-economic development of a country. Shuaibu and Lawong (2016) using a dynamic modelling approach concluded that the impact of insecurity is relatively higher on the external sector and fiscal variables compared with domestic policy variables.…”
Section: Empirical Literature Reviewmentioning
confidence: 63%
“…A similar study by Olusegun (2016) shows that security and other related variables do not only contribute positively to economic growth in Nigeria. In the same vein, Ifeoma, Ndubuisi-Okolo and Anagbogu (2015) reached the same conclusion emphasizing that security challenges retards the socio-economic development of a country. Shuaibu and Lawong (2016) using a dynamic modelling approach concluded that the impact of insecurity is relatively higher on the external sector and fiscal variables compared with domestic policy variables.…”
Section: Empirical Literature Reviewmentioning
confidence: 63%
“…This is despite Global Peace Ranking that Nigeria is among the most unsecured and complex security environment in West Africa. And insecurity situations alarms raised by Achumbe et al (2013), Okonkwo et al (2015), Adamu and Rasheed (2016), Ajodo-Adebanjoko and Okorie (2014) etc. However, it should be noted that Nigeria with vast land mass and also largely populated.…”
Section: Discussion Of Results and Implication For Agriculture Sectormentioning
confidence: 99%
“…In a similar study, Okonkwo et al (2015) argue that insecurity constitute threat to lives and property, hinders business activities and discourages local and foreign investors with consequential negative effects that retards socio-economic development of the country. In a study on security challenges and economy of Nigerian state, Nwagboso (2012) using mostly secondary data argued that failure of successive government to address problems related to poverty, unemployment, inequitable distribution of income among different ethnic nationalities in the country gave birth to the insecurity problems we are experiencing now.…”
Section: Research Hypotheses (I)mentioning
confidence: 95%
See 1 more Smart Citation
“…It is noted that the Nigerian incessant security threats are undermining the country's economic prospects. Therefore, there`s a need for partnership in counter-terrorism and insecurity in Nigeria, and it is inevitable because peace and security are vital to the development, and the national structural and transformation agenda of the current Nigerian administration may not be achieved if instability keeps perpetrating in the country (Ifeoma et al, 2015). Furthermore, in the previous years, violence consumed the country's north-western region due to ongoing abductions carried out by faction locally termed "Bandits."…”
Section: Implications Of Kidnapping To Nigerian Image In International Communitymentioning
confidence: 99%